LITERATION OF EDUCATION AND INNOVATION BUSINESS ENGINEERING TECHNOLOGY - A SAHARUDDIN; Tri Wijaya; Elihami Elihami; Ibrahim Ibrahim (Universitas Muhammadiyah Enrekang, 2019)
The low level of Indonesian Human Resources is due to the lack of mastery of educational technology Literacy and Entrepreneurial Innovation, due to the mental attitude and mastery of Education Technology and Entrepreneurship Innovation Technology that can be subjected to or agents of reliable development. Within the framework of globalization, education preparation needs to be synergized with the demands of competition. Therefore the dimension of competitiveness in Literacy in educational technology and Entrepreneurial Innovation is increasingly becoming an important factor so that efforts to spur the quality of Human Resources through education are demands that must be put forward. With the mastery of Educational Technology Literacy and Entrepreneurship Innovation, people will be able to compete in the era of globalization. The ability to master Education Technology Literacy and Entrepreneurship Innovation in general must be owned by the community, especially residents of slums along the river floods in Enrekang Regency. Therefore, awareness is needed among academics to participate in helping improve the quality of the Human Resources of the community through training.